Enabling health supply chains for improved well-being - Subramanian, Lakshmy (Taylor and Francis, 2020)
Health supply chains are necessary for effective health service delivery as they not only provide appropriate health outputs but also have the potentials to create and deliver cost-effective outcomes in line with the economic, social, and cultural conditions of a country. There is a need, therefore, to investigate ways to create functionally appropriate enabling environments that will largely be dependent upon the economic developmental levels in which health supply chains are considered. Under this backdrop, the current study helps in identifying the key enablers for the health supply chains which when present will contribute towards strengthening the health coverage and improving overall well-being. The enabling environment of health supply chains will include the broad structure within which individuals and organisations function. The different enablers are grouped into four broad categories namely (i) people and processes, (ii) systems and data, (iii) investments, and (iv) policies. The study attempts to delineate an integrated model of health supply chain enablers and their role in improving overall well-being. The model is further investigated with Kenya as a case study to understand the impact of the enablers on quality of life and improved well-being
Keywords: Quality of life; Well-being; enabling environment; Health supply chains